Sport, social media, and digital technology : sociological approaches - Sanderson, Jimmy (Research in the sociology of sport ;, 2022)
Social media and digital technologies have become significant forces in the sport industry. From athletes and fans interacting via social media and video games, sport organizations integrating these technologies into marketing and public relations functions, to coaches and athletic trainers using digital technology to monitor athletes' biometric information, these technologies are pervasive in sport. However, the literature at the intersection of sport and social and digital media lies almost exclusively in the domain of marketing and management. While these technologies are often championed for the benefits they offer in these functional areas, the effects and outcomes of these technologies have impacts on athletes, fans, and other society that warrant further attention. This volume brings together a collection of essays from leading global scholars working in diverse areas as sport sociology, sport management, sport media, and sport communication to illustrate how sociological approaches are imperative to enhancing our understanding of sport and social media and digital technology. Within this volume, scholars address topics such as gender, sexuality, racism, identity, politics, mental health, and surveillance and outline how sociological approaches to these topics offer important analyses that further our understanding of the comprehensive effects of social media and digital technology on sport stakeholders.